2022
DOI: 10.31083/j.fbl2707222
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Cytokine Response in the Contralateral Eye after First-Eye Cataract Surgery in Patients with Primary Angle-Closure Glaucoma, High Myopia or Type 2 Diabetes Mellitus

Abstract: Background: Bilateral sequential cataract surgery within a short period is becoming more prevalent because of the efficiency and safety of modern cataract surgery. It has been reported that the first surgical eye might affect the contralateral eye. This study investigated the cytokines involved in the immunopathogenesis of pre-existing ocular or systemic conditions, as well as the inflammatory biomarkers in response to topical stimuli, by analyzing the cytokine profile of aqueous humor (AH) from cataract patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Through the analysis of aqueous humor in patients with diabetes, high myopia, and primary angle-closure glaucoma, Jiancen Tang and colleagues discovered that IL-2 levels in the aqueous humor of the contralateral eye increased compared to the preoperative levels in the operated eye after surgery. This phenomenon was also con rmed in our animal experiments [30] .It is well known that IL-2, produced by T cells, is an immunoregulatory protein. IL-2 plays a crucial role in regulating the immune system, particularly in the proliferation, differentiation, and function of T cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Through the analysis of aqueous humor in patients with diabetes, high myopia, and primary angle-closure glaucoma, Jiancen Tang and colleagues discovered that IL-2 levels in the aqueous humor of the contralateral eye increased compared to the preoperative levels in the operated eye after surgery. This phenomenon was also con rmed in our animal experiments [30] .It is well known that IL-2, produced by T cells, is an immunoregulatory protein. IL-2 plays a crucial role in regulating the immune system, particularly in the proliferation, differentiation, and function of T cells.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in recent years, more and more teams have found that in non-diabetic patients, the aforementioned phenomenon and high expression of biological factors such as MCP-1 do not exist [28,29] .In diabetic patients, there is a signi cant increase in MCP-1 and substance P in the second eye [28,29] . Furthermore, when different diseases are combined, the expression of biological factors in the aqueous humor before and after surgery varies among patients [30] .Therefore, in patients with systemic diseases, there are inherent differences in the AH environment.…”
Section: Introductionmentioning
confidence: 99%
“…IgG N-glycome profiling by matrix-assisted laser desorption/ ionization time of flight mass spectrometry, raw matrix-assisted laser desorption/ionization time of flight mass spectrometry data processing, and circulating inflammatory markers measurement (cytokine assay) were conducted according to previous reports 16,[20][21][22][23] and are described in detail in the Supplemental Material.…”
Section: Mass Spectrometric Igg N-glycomics and Cytokine Assaymentioning
confidence: 99%
“…Inflammatory marker measurements were performed without knowledge of the CHIP status of the patients. Profiling of the inflammatory marker of circulating cytokines and IgG galactosylation (IgG-Gal) ratio was performed according to published protocols, [27][28][29] detailed methods were in Supplemental Material.…”
Section: Inflammatory Marker Measurementsmentioning
confidence: 99%